2015
DOI: 10.7771/1932-6246.1154
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Transformation and Cognitive Processes in Origami Paper Folding

Abstract: Research on problem solving typically does not address tasks that involve following detailed and/or illustrated step-by-step instructions. Such tasks are not seen as cognitively challenging problems to be solved. In this paper, we challenge this assumption by analyzing verbal protocols collected during an Origami folding task. Participants verbalised thoughts well beyond reading or reformulating task instructions, or commenting on actions. In particular, they compared the task status to pictures in the instruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 72 publications
1
22
0
1
Order By: Relevance
“…Hand configurations were not specified in this study, but the direction of folding was (e.g., "fold the tip diagonally to the left"). They measured folding success by subjective ratings of figure similarity, and found that people who read fewer instructions aloud were more successful [73]. This result suggests that internalising visual representations is a key process in action imitation [78], and that verbal instructions can actually hinder learning.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Hand configurations were not specified in this study, but the direction of folding was (e.g., "fold the tip diagonally to the left"). They measured folding success by subjective ratings of figure similarity, and found that people who read fewer instructions aloud were more successful [73]. This result suggests that internalising visual representations is a key process in action imitation [78], and that verbal instructions can actually hinder learning.…”
Section: Discussionmentioning
confidence: 97%
“…An earlier study [73], presented origami folding instructions as a sequence of written instructions with pictures of the folding shown from the Beside viewpoint. They found that when people learn to fold origami from such pictorial-verbal instructions, they creatively interpret the instructions by reformulating them into spatial terms and adding information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants in the KEP+MCP and MCP groups received the multicomponent intervention that consisted of music therapy [ 23 ], art therapy [ 24 ], horticulture therapy [ 25 ], handicraft [ 26 ], recreational therapy [ 27 ], stretching [ 28 ], laughing therapy [ 29 ], and activity therapy [ 30 ]. Each MCP intervention was conducted by professional therapists for 60 min per session twice a day, 5 days per week for 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…Treat each step as one unit: First identify the position and orientation of the current model, take steps, and then confirm the new position. Make sure each child has done this step correctly before proceeding to the next step [13]. If the child feels difficulty, then the steps to fold must be repeated.…”
Section: ) Fifth Stage (Five Folds Make the Head Of The Car)mentioning
confidence: 99%